Wind tunnel and delayed detached eddy simulation investigation of interference between two tall buildings. Issue 9 (July 2019) - Sharma, Ashutosh; Mittal, Hemant; Gairola, Ajay
In urban areas, the wind load on a tall building is significantly influenced by the nearby building. The neighboring buildings change the dynamics of the incident flow, which affects the distribution of load on the principal building. The wind-induced loads under the effect of interference may amplify or shield depending on various factors. The present work first examines the impact of height ratios of the interfering building through wind-tunnel tests. The characteristics of time-mean and fluctuating forces for aerodynamically modified tapered twin buildings (having the same shape and size) are analyzed. Second, in the last section, it adopts a delayed detached eddy simulation–based numerical simulation approach to study the flow field in tandem, parallel, and staggered arrangements of square buildings. The results show that as the height of the interfering building decreases, the shielding effect decreases. It obtains the regression equations of interference factor from the best-fit curve.